Funkcjonowanie rynku instrumentów pochodnych na warszawskiej Giełdzie Papierów Wartościowych - Rosiek, Janusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The paper presents sorts of derivative instruments. We have contact with them in the worldwide exchange trade. Derivative transactions begin to play a more important role also in the Polish capital market. They constitute an alternative concerning investment of assets in shares with higher investment risk or investments in safety bonds with low level of profitability. The second part of the paper presents the formation of derivative instruments turnover on the Warsaw Stock Exchange between 2000 and 2005. The author focuses on their profitability and the growing meaning of that kind of transactions in the exchange trade. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 545-555